People’s knowledge and dependency on Rampur wetland of western Chitwan, Nepal - Nepal, Rajesh; Dangol, Dharma Raj (Journal of Natural History Museum, 2018)
Understanding people’s knowledge and their dependency on wetland forms the basis of conserving them. The paper assessed the status of wetland in Rampur and local peoples’ dependency on it, conducted in the year of 2013. Study revealed that majority of respondents noticed change in wetland in past years and in their priority, drying ranked first followed by decrease in acreage, and biodiversity loss. It was found that factors responsible for these changes were drought, encroachment, flooding, erosion and succession by invasive weed species. Study found that local peoples have several impacts on wetland which were conversion for agriculture, discharge of pollutants, overexploitation of aquatic resources, overgrazing conversion for residential development, and conversion for aquaculture. However, Negative impacts of wetland were flooding, foul smell, incidence of insect pest/disease, coldness in winter, and bank cutting. It was found that people dependent on wetland for farming, fodder collection, fuel wood collection, medicinal plants, religious purpose, fishery, livestock grazing, wild edible plants, irrigation, commercial fishery and recreation. Study showed that local peoples have knowledge about several aspects of wetland and they are dependent for their livelihood. Therefore, in order to protect wetland from degradation, conservation and management activities need to be implemented properly with the involvement of local peoples.